2016
DOI: 10.1515/med-2016-0092
|View full text |Cite
|
Sign up to set email alerts
|

Use of a simplified consent form to facilitate patient understanding of informed consent for laparoscopic cholecystectomy

Abstract: AbstractBackgroundSurgical informed consent forms can be complicated for patients to read and understand. We created a consent form with key information presented in bulleted texts and diagrams combined in a graphical format to facilitate the understanding of information during the verbal consent discussion. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 49 publications
0
14
0
1
Order By: Relevance
“…Borello et al (1) prepared ICFs that were made easier to comprehend with marked texts and diagrams for laparoscopic cholecystectomy and reported that these forms are easier to understand and remember. Shukla et al (25) reported that the cataract surgery ICFs at the second-grade reading level and video support are easier to understand.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Borello et al (1) prepared ICFs that were made easier to comprehend with marked texts and diagrams for laparoscopic cholecystectomy and reported that these forms are easier to understand and remember. Shukla et al (25) reported that the cataract surgery ICFs at the second-grade reading level and video support are easier to understand.…”
Section: Discussionmentioning
confidence: 99%
“…Informed consent means the authorization given to the health professional for the diagnosis or treatment interventions planned with the patient's consent. Informed consent forms (ICF), being an inseparable constituent of the consent phase, are used to help the patients during the treatment phase by explaining the indications, advantages, and possible risks of medical applications (1). It was also shown that these texts may be effective in solving problems in the treatment phase with advantages such as providing the patient-doctor communication and making the agreement of the patient to treatment easier (2,3).…”
Section: Introductionmentioning
confidence: 99%
“…Another essential requirement is the consent of the person concerned, subject to adequate information regarding the conditions of the operation, the possible risks associated with such practices, the precautions to be taken after receiving a tattoo or piercing and the eventual subsequent removal of the same. Consent of the person concerned is essential for the operator to intervene on his/her body [ 9 ]. However, this consent may never be valid to authorise an activity contrary to Art.…”
Section: Resultsmentioning
confidence: 99%
“…In previous studies, it was reported that these forms were made easier with marked texts and diagrams so that ICFs could be understood and remembered more easily and these video supported forms were more understandable and easier to remember [3,20].…”
Section: Discussionmentioning
confidence: 98%